The Influence of Workplace Layout and Non-Physical Work Environment on BLU UPTD Trans Semarang Employees’ Performance - Syakira Zakiyyatul Miskiyah; Umar - Farouk; Taviyastuti - Taviyastuti (Admisi dan Bisnis, 2021)
Nowadays in a competitive business environment, companies should prioritize the ability of their workforce. BLU UPTD Trans Semarang is a unit of Semarang Transportation Agency that is committed in fulfilling the need for proper public transportation facilities. This company focus on employees’ performance, everything which might affect it, and how to improve it. However, the employees’ performance had continued to fluctuate in the period from January to March 2020. Therefore, BLU UPTD Trans Semarang has to give more attention to increase the employees’ performance. The factors that might affect employees’ performance are workplace layout and non-physical work environment. The objective of this research is to analyze how is the influence of workplace layout and non-physical work environment on employees’ performance at BLU UPTD Trans Semarang. The research model is using multiple linear regression and SPSS 25. The sampling method of this research is purposive sampling by using work period criteria. The number of samples is 51 employees. The results of the partial significance test show that workplace layout and non-physical work environment have a positive and significant effect partially on the employees’ performance. Meanwhile, the results of the simultaneous significance test show that workplace layout and non-physical work environment have a significant effect simultaneously on employees’ performance. Based on the results of the coefficient of determination, workplace layout and non-physical work environment have a contribution effect of 67.6% which means they have a big influence on employees’ performance. BLU UPTD Trans Semarang should improve their arrangement of workplace layout and create a conducive non-physical work environment to increase the employees’ performance.